Orthodontic screening and referral practices of dental therapists in New Zealand - Lim Nadarren; Bennani Florence; Mei Li; Thomson William Murray; Farella Mauro; Antoun Joseph Safwat (Sciendo, 2017)
Timely referrals of appropriately screened cases are essential for the effective delivery of orthodontic treatment. Dental therapists are intimately involved with the orthodontic screening process in New Zealand, given that they are the primary oral health providers for child and adolescent patients.